SEPTIC ARTHRITIS AFTER TOTAL KNEE REPLACEMENT IN GERIATRICS PATIENT, THE IMPORTANT OF PERIOPERATIVE CARE - Jaya, Kris; Alexander, Devin; Rianto, Louis (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2021)
Introduction: The geriatric population are the fastest growing segment around the world. The prevalence of multiple comorbidities in geriatric patients requiring special perioperative care. Perioperative management must be done properly, considering that surgical complications on geriatric can cause multiple comorbidities. There are many complications that often occur in geriatrics, one of which is infection.Case report: A 77-year-old man complained about pain on his right knee 1 â€“ 2 weeks after doing TKR procedure. The pain accompanied with fever, swollen, and redness. Physical examination showed elevated blood pressure (140/90), Fever (37,4oC), obesity grade I (BMI 27.4 kg/m2), swollen and redness on his right knee, pain on palpation with VAS 5, edema (+). Barthel index ADL showed mild dependency, FRAIL score 3, qSOFA score 0. Laboratory result showed elevated leukocyte 14.900/Âµl.Conclusion: Geriatric patients are very vulnerable to the risks of surgery, one of which is septic arthritis. So that a good perioperative evaluation can reduce complications, comorbidities and decreased functional status